2015
DOI: 10.3109/13880209.2014.959611
|View full text |Cite
|
Sign up to set email alerts
|

Biological activities of salvianolic acid B fromSalvia miltiorrhizaon type 2 diabetes induced by high-fat diet and streptozotocin

Abstract: (2015) Biological activities of salvianolic acid B from Salviamiltiorrhiza on type 2 diabetes induced by high-fat diet and streptozotocin, Pharmaceutical Biology, 53:7, 1058-1065, DOI: 10.3109/13880209.2014 The results indicate that SalB can inhibit symptoms of diabetes mellitus in rats and these effects may partially be correlated with its insulin sensitivity, glycogen synthesis and antioxidant activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 25 publications
2
35
0
Order By: Relevance
“…Sal B is a typical bioactive compound isolated from Danshen. A recent study indicated that Sal B can inhibit symptoms of DM in rats and these effects may partially be correlated with its insulin sensitivity, glycogen synthesis, and antioxidant activity (Huang et al 2015). However, there is little about possible signaling pathway of Sal B on DM.…”
Section: Discussionmentioning
confidence: 99%
“…Sal B is a typical bioactive compound isolated from Danshen. A recent study indicated that Sal B can inhibit symptoms of DM in rats and these effects may partially be correlated with its insulin sensitivity, glycogen synthesis, and antioxidant activity (Huang et al 2015). However, there is little about possible signaling pathway of Sal B on DM.…”
Section: Discussionmentioning
confidence: 99%
“…There are many approaches to efficiently decrease blood glucose level such as promoting insulin secretion [24], inhibiting glucose absorption [25], stimulating glucose uptake by tissues [26] and increasing insulin sensitivity [27]. Insulinotropic agents such as glibenclamide, stimulate insulin secretion and dramatically decrease blood glucose level in both normal and diabetic animals.…”
Section: Discussionmentioning
confidence: 99%
“…Although its most common use is in the treatment of cardio-cerebral vascular diseases [14][15][16], Sal B is recently reported to possess a number of potential implications in the treatment of insulin resistance, obesity, and type 2 diabetes [17][18][19][20]. Sal B or Salvia miltiorrhiza extract improved glycemic control, dyslipidemia, and insulin sensitivity in high fat diet and streptozocin-induced type 2 diabetic rats [17,19]. Furthermore, Sal B can moderate lipids and reduce obesity in high-fat diet-induced obese C57BL/6J mice by suppressing peroxisome proliferator-activated receptor gamma (PPARγ)-mediated adipogenesis [18].…”
Section: Introductionmentioning
confidence: 99%